Development of copy number assays for detection and surveillance of piperaquine resistance associated plasmepsin 2/3 copy number variation in Plasmodium falciparum - Ansbro, MR; Jacob, CG; Amato, R; Kekre, M; Amaratunga, C; Sreng, S; Suon, S; Miotto, O; Fairhurst, RM; Wellems, TE; Kwiatkowski, DP (Springer Nature, 2020)
Background: Long regarded as an epicenter of drug-resistant malaria, Southeast Asia continues to provide new challenges to the control of Plasmodium falciparum malaria. Recently, resistance to the artemisinin combination therapy partner drug piperaquine has been observed in multiple locations across Southeast Asia. Genetic studies have identified single nucleotide polymorphisms as well as copy number variations in the plasmepsin 2 and plasmepsin 3 genes, which encode haemoglobin-degrading proteases that associate with clinical and in vitro piperaquine resistance.